Prevalence of common symptoms of neonatal illness in Northwest Ethiopia: A repeated measure cross-sectional study. - Tadesse Guadu Delele; Gashaw Andargie Biks; Solomon Mekonnen Abebe; Zemene Tigabu Kebede (PLoS ONE)
Background The neonatal period is the most vulnerable stage of life. In Ethiopia, neonatal illness is common and the reduction in neonatal mortality is not as significant as for under-five mortality. Objectives To determine the prevalence and factors associated with neonatal illness symptoms reported by mothers delivering in health facilities in Northwest Ethiopia. Methods A repeated measure cross-sectional study design was employed to collect data from 358 randomly selected deliveries in 11 health facilities from November 2018 to March 2019. A pretested and interviewer-administered structured questionnaire adapted from the literature was employed to record neonatal outcomes (illnesses and/or deaths) at birth, 24 hours, 7th, 14th and 28th day from birth. Cleaned data was exported to STATA version 14 software for analysis. Multilevel analysis was used to identify individual and facility-level characteristics associated with neonatal illness symptoms. Results The prevalence of neonatal illness symptoms was 27.8% (95% CI; 23.2, 32.8) of the 338 babies born alive and the neonatal mortality rate was 41/1000 live births (14/338). The most common symptoms or conditions of neonatal illness reported by mothers' in the study area were possible serious bacterial infections (95.8%, 90/94), localized bacterial infections (43.6%, 41/94), low birth weight (23.4%, 22/94), diarrhea (18.1%, 17/94), prematurity (14.9%, 14/94), and jaundice (7.5%, 7/94). Among the babies who died, neonates who had possible serious bacterial infections, low birth weight, localized bacterial infections, and prematurity took the highest proportions with 100% (14/14), 64.3% (9/14), 50% (7/14), and 42.9% (6/14), respectively. Having a maximum of 3 children (AOR = 1.96; 95% CI = 1.1-3.6), having twins or triplets during pregnancy (AOR = 2.43; 95% CI = 1.1-6.1), and lack of antenatal counseling (AOR = 1.83; 95% CI = 1.1-3.3) were among the maternal factors associated with neonatal illness. Having low birth length (AOR = 7.93; 95% CI = 3.6-17.3), and having a poor breastfeeding quality (AOR = 2.37; 95% CI = 1.4-4.0) were found to be the neonatal factors associated with neonatal illness. Conclusions This study indicated a high prevalence of neonatal illness symptoms in Northwest Ethiopia. Therefore, early detection, referral and better management of symptoms or conditions with a high mortality, like sepsis and low birth weight are compulsory to save the lives of many neonates. Strengthening the health extension programme to improve antenatal care service utilization and breastfeeding quality of neonates among postpartum women is crucial.